2019
DOI: 10.2174/2215083805666190705170022
|View full text |Cite
|
Sign up to set email alerts
|

Carica papaya: Potential Implications in Human Health

Abstract: Background: Carica papaya, a tree-like herb, is cultivated in more than 50 tropical and subtropical countries worldwide. The parts [leaves, fruit (ripe and unripe), seeds and latex] are used as food as well as traditional medicine in several ways for a number of diseases. Papaya, with a variety of phytochemicals like carotenoids, polyphenols, benzyl isothiocynates, benzyl glucosinates, prunasin (cyanogenic substrate), papain and chymopapain, alkaloids, phenolic compounds, flavonoids, vitamins (A, C, E), carote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Traditionally, papaya fruits have had different usages depending on the need, e.g., papaya root juice has been used to treat boils, burns, and warts [6]; papaya fruits and leaves contain protein-digesting enzymes such as papain and chymopapain, which have proven their effect on injured skin tissue, removing damaged tissues from wounds and limiting infections [7][8][9]. A recent study reported by Logozzi et al [10], showed that fermented papaya preparations (specifically the commercialized product FPP ® ) induced increase in telomeres length in bone marrow and ovary, together with an increase in the plasmatic levels of telomerase activity and antioxidant levels, with an efficient decrease in radical oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, papaya fruits have had different usages depending on the need, e.g., papaya root juice has been used to treat boils, burns, and warts [6]; papaya fruits and leaves contain protein-digesting enzymes such as papain and chymopapain, which have proven their effect on injured skin tissue, removing damaged tissues from wounds and limiting infections [7][8][9]. A recent study reported by Logozzi et al [10], showed that fermented papaya preparations (specifically the commercialized product FPP ® ) induced increase in telomeres length in bone marrow and ovary, together with an increase in the plasmatic levels of telomerase activity and antioxidant levels, with an efficient decrease in radical oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition activity was more important for fungi (16.5 to 60 mm) than bacteria (10 to 20 mm). Antimicrobial activities of papaya seeds essential oils was also previously proved (Tapsoba and Deschamps, 2006;Singh and Ali, 2011;Muhamad et al, 2017;Zhang and Chen, 2017;Seshamamba et al, 2018;Heena and Sunil, 2019;Chai et al, 2020;Dotto and Abihudi, 2021;Li et al, 2021;Yi et al, 2022). The inhibition diameter for all Candida strains is higher than those of all commercial antibiotics and also higher than those found by He et al (2017) which was less than 34 mm.…”
Section: Discussionmentioning
confidence: 65%
“…Due to associated side effects and high cost of treatment with the present treatment modalities, and stable increase in the incidence of new cancer cases and cancer mortality, the quest to search for cheaper and effective alternatives began leading to an increased interest in traditional herbal therapeutics using plants and their derivatives. Papaya leaves have been used for the treatment of malaria (Krishna et al, 2008), asthma (Gammulle et al, 2012), dengue fever (Ahmad et al, 2011;Subenthiran et al, 2013), vitamin B1 de iciency (Vien and Thuy, 2012), including cancer in many parts of the world (Heena and Sunil, 2019;Soubra et al, 2016). It also has shown antiproliferative and cytotoxic activities against colorectal (Lohsoonthorn and Danvivat, 1995) and gall bladder cancers (Pandey and Shukla, 2002), prostate cancers Shahar et al (2011), cervical cancer (Siegel et al, 2010) and breast cancers (Zhang et al, 2009;García-Solís et al, 2009) , while its extracts from seeds and the fruit show activity against MCF-7, HepG2, HL-60 cancer cells (breast, liver, leukemia, respectively) (Jayakumar and Kanthimathi, 2011).…”
Section: Methodsmentioning
confidence: 99%